2013
DOI: 10.1038/cddis.2013.36
|View full text |Cite
|
Sign up to set email alerts
|

B-Myb switches from Cyclin/Cdk-dependent to Jnk- and p38 kinase-dependent phosphorylation and associates with SC35 bodies after UV stress

Abstract: B-Myb is a highly conserved member of the Myb transcription factor family that has essential roles in cell-cycle progression. Recent work has suggested that B-Myb is also involved in the cellular DNA-damage response. Here, we have investigated the fate of B-Myb in UV-irradiated cells. UV stress leads to the appearance of phosphorylated B-Myb in nuclear SC35 speckles during transcriptional shutdown. Furthermore, we show that UV irradiation leads to a change of the phosphorylation pattern of B-Myb, which is caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 52 publications
0
12
0
2
Order By: Relevance
“…We have previously reported that UV-irradiation or heat stress induces association of a modified form of B-Myb phosphorylated at Thr-487 with so-called SC35 nuclear speckles 30 . The UV-induced SC35 speckle association of B-Myb described previously is clearly distinct from the immediate recruitment of B-Myb to sites of DNA-damage shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that UV-irradiation or heat stress induces association of a modified form of B-Myb phosphorylated at Thr-487 with so-called SC35 nuclear speckles 30 . The UV-induced SC35 speckle association of B-Myb described previously is clearly distinct from the immediate recruitment of B-Myb to sites of DNA-damage shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, B-Myb is required for the recovery from a DNA-damage induced cell cycle arrest 29 . More recently, we have observed that UV irradiation leads to a switch from Cyclin/Cdk-dependent to Jnk- and p38 kinase-dependent phosphorylation of B-Myb, thereby changing the phosphorylation status of B-Myb 30 . However, the exact role of B-Myb in the DNA-damage response has not been revealed by these studies.…”
mentioning
confidence: 99%
“…involved in cell cycle progression and is recruited to nuclear speckles in response to UVC, concomitant with a switch in its phosphorylation patterns. 55 Interestingly, B-Myb has also been reported to be required for S-phase entry and to interact with Poldip1, a Pol δ-interacting protein. 56 hOGG1 is a DNA glycosylase involved in the initial step of base excision repair of oxidized purines, and APE1 catalyzes the next step.…”
Section: Discussionmentioning
confidence: 99%
“…Initial efforts to link phosphorylation of certain sites to specific B-Myb functions have been inconclusive, resulting in the current ‘all-or-nothing’ model of B-Myb activation by phosphorylation. We have recently shown that B-Myb adopts distinct phosphorylation patterns upon DNA damage, which correlates with transcriptional shutdown during recovery time (23). These findings suggest that different functions of B-Myb are modulated by specific phosphorylation patterns, prompting us to investigate the cell cycle-dependent phosphorylation of B-Myb in more detail.…”
Section: Introductionmentioning
confidence: 99%